Role of IL-10 and IL28B in HCV Infected Patients: A Short Review - Amar Deep; Ajay Kumar; Suchit Swaroop (International Journal of Life Sciences, 2017)
The hepatitis C virus (HCV) infection is pandemic and has been systematically studied, characterized in North America and Europe, but this important public health problem has not received tantamount attention in other regions. Hepatitis C virus (HCV) was detected from the serum of infected animal by Choo et al (1989), it is now well accomplished that HCV infection pretends all countries, leading to a major global health problem that requires far-flung active interventions for its prevention and control. Subsequently HCV infection, the innate immune response is initially important for controlling viral replication with the adaptive immune reaction topping out at 8–weeks after infection. Finally, a coordinated attempt between the innate and adaptive immune responses is necessary to eliminate HCV from the liver. Cytokines play an important role in the regulation of immune response may influence the outcome of acute HCV infection. Interleukin-10 (IL-10) is having multiple function anti-inflammatory cytokine mainly produced by immune cells, such as T cells, monocytes, appropriately stimulated macrophages, some subsets of dendritic cells (DCs), and B cells. IL28B gene encodes a cytokine distantly related to type I interferon and the IL-10 family. IL-10, interleukin 28B (IL28B), and interleukin 29 (IL29) are three closely related cytokine genes that form a cytokine gene cluster on a chromosomal region mapped to 19q13. Expression of the cytokines encoded by the three genes can be induced by viral infection.